Estimation of the Folic Acid Using Zero Order, Area Under Curve and First Derivative Spectrophotometric Methods in Pure and Marketed Tablet Formulations - Al beea, Ruba F; Abbas, Hend A; Taqi, Rawa M. M; Abdulabbas, Dhifaf A; Abed, Marwah A (Al-Nahrain Journal of Science, 2017)
Three simple, inexpensive and nontoxic spectrophotometric methods have been used for determination folic acid in pure and market formulation tablets. Linearity was founded in the range 6- 20 mg.l-1 for the all three methods, the detection limits was found to be 0.261 for zero order method, 0.006 for AUC method and 3.800 for first derivative method. The RSD% was found to be less than 0.856 indicating a good accuracy and precision of three proposed methods. The results of zero order, AUC and first derivative methods were statistically compared with those obtained by the official standard method using the F-test and t-test and found to be a good agreement.